2013
DOI: 10.1155/2013/925876
|View full text |Cite
|
Sign up to set email alerts
|

Slip Effects on Pulsatile Flow of Blood through a Stenosed Arterial Segment under Periodic Body Acceleration

Abstract: A theoretical investigation concerning the influence of externally imposed periodic body acceleration on the flow of blood through a time-dependent stenosed arterial segment by taking into account the slip velocity at the wall of the artery has been carried out. A mathematical model is developed by treating blood as a non-Newtonian fluid obeying the Casson fluid model. The pulsatile flow is analyzed by considering a periodic pressure gradient and the inertial effects as negligibly small. A suitable generalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Sinha et al [13] did a study on the slip and periodic body acceleration effect on pulsatile flow of blood passing through a segmented stenosed artery. Tripathi and Sharma [14] did a study on heat and mass transfer effects of a blood flow two phases which is pulsatile past a stenosed artery that is narrow with chemical reaction and radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Sinha et al [13] did a study on the slip and periodic body acceleration effect on pulsatile flow of blood passing through a segmented stenosed artery. Tripathi and Sharma [14] did a study on heat and mass transfer effects of a blood flow two phases which is pulsatile past a stenosed artery that is narrow with chemical reaction and radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Saddiqui, et al [15] studied the effect of both the slip velocity and body acceleration on the pulsatile blood flow on a casson fluid though an artery with stenosis. Sinha et al [16] did a study on the effect of slip on pulsatile blood flow through an artery with stenosed segment with the influence of body acceleration that is periodic. Considering the slip velocity at the wall of the artery the body acceleration which is periodic, has an influence on the blood flow through an artery with a stenosed segment that is time dependent.…”
Section: Introductionmentioning
confidence: 99%
“…They found that temperature field reduces with the enhancement of the slip parameter and Jeffrey parameter. Sinha et al [19] examined the influence of slip on flow of blood in a constricted artery under the impact of body acceleration. They showed that flow resistance enhances with the stenosis height increase and velocity slip increase.…”
Section: Introductionmentioning
confidence: 99%